SAFETY ASSESSMENT OF CRUDE AND AQUEOUS EXTRACTS OF Syzygium aromaticum in Oreochromis niloticus (Linnaeus, 1758) JUVENILES - DUROJAIYE, A.F; OBASA, S.O.; OLUSESI , A.S. (Nigerian Journal of Fisheries, 2023)
The application of plant extracts in aquaculture is growing due to their various biological benefits; however, some are toxic. This study was carried out to evaluate the safety doses of S. aromaticum (clove buds) in O. niloticus juvenile. Air dried buds were pulverized to obtain crude powder while aqueous extraction was done following standard method to obtain aqueous extract. Median lethal dose (LD50) was determined using Lorke’s method. Behavioural responses were monitored and recorded. When crude powder was administered, there was no adverse reaction observed in the first 6 hours at doses below 1000mg/kg while reactions like weak swimming, loss of scale and fin erosion were noted at increased doses. In the group administered aqueous extract, no adverse responses were recorded in the first 6 hours. Beyond this period, ragged fins, slow opercular movement and loss of scale were observed even at the lowest dose of 10mg/kg. The calculated LD50 for crude powder was 223.61mg/kg and 538.52mg/kg for aqueous extract. Conclusively, the LD50 values recorded in this study indicate moderate toxicity. It is recommended that S. aromatica be used with caution and the calculated LD50 should not be exceeded to avoid toxic responses from fish.